Rare earth oxide modified fly ash hollow microspheres and preparation method thereof

By adding anionic dispersant to the ball mill and controlling the pH value, combined with spray granulation method and high-temperature burning, hollow microspheres of oxidized rare earth modified fly ash were successfully prepared, which solved the high firing temperature and mullite formation. The problem of high temperature has achieved efficient and low-cost reuse of fly ash resources.

CN119406895APending Publication Date: 2025-02-11HANGZHOU RULIN NEW MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411559305.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to successfully prepare hollow microspheres of oxidized rare earth modified fly ash by spray granulation. The existing methods for preparing rare earth modified fly ash include high firing temperature, high mullite phase generation temperature and manufacturing cost. High problem.

Method used

The spray granulation method is used to prepare oxidized rare earth modified fly ash hollow microspheres. By adding anionic dispersant with COO-groups to the ball mill, the pH value of the ball mill is controlled to completely dissolve the COO-group of the dispersant. The dispersion of powder particle size smaller than the set value is increased, and the polarization characteristics of oxidized rare earths are used to reduce the firing temperature during high-temperature burning.

Benefits of technology

The prepared oxide rare earth modified fly ash hollow microspheres have light weight, heat insulation, sound insulation, corrosion resistance, low thermal conductivity and excellent low frequency performance. The firing temperature is reduced, the mullite phase generation temperature is reduced, and the compressive strength is improved. , the thermal conductivity is reduced by more than 10%, and energy consumption is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406895A_ABST
    Figure CN119406895A_ABST
Patent Text Reader

Abstract

The invention discloses rare earth oxide modified fly ash hollow microspheres and a preparation method thereof, and belongs to the field of solid waste resource reutilization. The rare earth oxide modified fly ash hollow microspheres are prepared by adopting a spray granulation method, the fly ash and rare earth oxide mixed powder is subjected to grinding, spray granulation and high-temperature firing in water to prepare the rare earth oxide modified fly ash hollow microspheres, and the hollow microspheres have the advantages of light weight, heat insulation, sound insulation and excellent low-frequency performance; the method has a good application prospect in the fields of light thermal insulation materials, thermal insulation plates, sewage purification, sound absorption materials, drug sustained-release and controlled-release bodies, catalyst carriers, photoelectric materials and the like, and an industrial production technology is provided for high-value utilization of fly ash.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to rare earth oxide modified fly ash hollow microspheres and a preparation method thereof, and belongs to the field of solid waste resource recycling. Background Art

[0002] Fly ash is the fine solid particles in the flue gas ash produced by coal combustion and is the main solid waste discharged by thermal power plants. At present, fly ash is mainly used in the production of building materials, road construction, photocatalysis, agriculture, sewage treatment, etc. Therefore, the active and efficient use of fly ash is of great significance to saving land, protecting the environment and implementing a sustainable development strategy.

[0003] The floating beads floated from fly ash have many excellent physical and chemical properties, such as light weight, high strength, thermal insulation, good fluidity, corrosion resistance, low thermal conductivity and shrinkage, good electrical insulation and thermal stability. It is an emerging functional material, showing broad application prospects in the fields of thermal insulation and refractory materials, building materials, wave absorption, sound insulation, plastics, rubber, coatings, chemicals, environment, metallurgy, navigation and aerospace, with good economic and social benefits. However, the content of floating beads in fly ash is generally 1%-3%, but the market demand for floating beads is increasing.

[0004] The American company Flyt developed hollow fly ash balls and realized industrialization. Due to the advantages of abundant fly ash raw materials and low prices, fly ash was prepared into hollow microspheres, which solved the problems of fly ash treatment and resource utilization and alleviated the shortage of floating beads in the market. Patent CN104310787A invented a method for preparing artificial hollow fly ash floating beads. Fly ash powder was mixed with water, stabilizer, and foaming agent and ball milled, and then spray granulated and sintered to form fly ash hollow microspheres. The average density of the hollow microspheres is 0.6-0.7g / cm 3 , the particle size is 10-100μm. After spray granulation, the invention needs to be heated in a special beading furnace to obtain hollow floating beads, which limits the heating treatment equipment; at the same time, the floating method is required to separate the hollow floating beads. The purpose of the floating method is to separate the hollow floating beads from the powder particles, indicating that the prepared hollow floating beads contain powder. Patents CN101870588 B and US 8845936B2 invented a method and device for preparing hollow ceramic microbeads, and prepared fly ash hollow microspheres with a particle size of 10-100μm. The hollow ceramic bead shell prepared in this patent has many pores, and no closed hollow ceramic beads are found. Wang Qinggang et al. used a spray drying method to make microbeads from fly ash. The adsorption amount and removal rate of the microbeads after calcination at 800°C for methyl violet were 24.09mg / g and 96.4%, respectively. This document shows that it contains unformed powder and broken microbeads, the powder slurry fails to completely prepare hollow microbeads, and the optimal adsorption capacity of the microbeads for methyl violet in wastewater needs to be improved.

[0005] At present, there are two methods for rare earth modified fly ash. One is to immerse fly ash or solid fly ash balls in rare earth chloride solution to form surface modification and use it as a wastewater purifier. The density of the surface modified fly ash powder or solid ball is greater than 1g / cm 3 It is very easy to settle in the wastewater, which reduces the adsorption effect of harmful impurities in the wastewater. In addition, the impregnated rare earth chloride is easily soluble in water. In the wastewater, the rare earth chloride falls off from the surface of the fly ash powder or solid balls and dissolves into the wastewater, which also reduces the impurity removal effect; the other is to add rare earth oxide or rare earth carbonate to the fly ash to prepare the grouting material of the thermal insulation material or the rare earth modified solid ball expanded clay. Patent CN117229078 B invented a method for reducing the firing temperature of high-refractory ceramsite by using rare earth oxides. According to the content of silicon oxide and aluminum oxide in fly ash, a high aluminum oxide compound is added to adjust the aluminum-silicon ratio. The prepared powder is mixed with rare earth oxide and a binder is added to form balls and roasted to obtain fly ash ceramsite. The addition of rare earth oxide reduces the firing temperature of fly ash ceramsite and increases the density of fly ash ceramsite. This method requires the use of aluminum oxide and silicon oxide to adjust the ratio of aluminum oxide to silicon oxide in fly ash. After the mixture, the mass ratio of aluminum oxide to silicon oxide is 0.7-1.6:1. In order to achieve this mass ratio, a large amount of aluminum oxide needs to be added, which increases the manufacturing cost and is not conducive to the recycling of fly ash. Spray granulation is a method for preparing hollow structural materials, but it has strict requirements on the dispersion stability of slurry. Since the dispersion stability of rare earth oxide and fly ash in slurry is greatly affected by the zeta potential, particle size, content, dispersant, pH, etc. of various compounds, there is no report on the successful preparation of rare earth oxide modified fly ash hollow microspheres by spray granulation. Selecting appropriate process parameters for different compounds to prepare stable dispersed slurry is a technical key and technical difficulty. Only highly dispersed slurry can be used to prepare hollow structural materials through spray granulation. Summary of the invention

[0006] In view of this, the purpose of the present invention is to overcome the shortcomings of the prior art and provide a rare earth oxide modified fly ash hollow microsphere and a preparation method thereof. The present invention adopts a spray granulation method to prepare the rare earth oxide modified fly ash hollow microsphere. The obtained hollow microsphere has light weight, heat insulation, sound insulation, corrosion resistance, low thermal conductivity, and excellent low-frequency performance, and has application prospects in the fields of lightweight refractory materials, thermal insulation materials and sound absorbing materials.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing hollow fly ash microspheres modified with rare earth oxide, which comprises the following steps:

[0009] 1) Slurry preparation: Add deionized water and COO into a ball mill stirring tank. -After the dispersion is evenly dispersed, the ball mill is turned on and fly ash and rare earth oxide mixed powder are gradually added. During the ball milling process, the pH value of the ball milling liquid is controlled to make the COO - The groups are completely dissociated. When the particle size of the powder in the ball milling liquid is smaller than the set value, the ball milling is stopped, and the ball milling liquid is transported to the spray granulation dispersion tank, and a binder is added. After high-speed dispersion, the slurry required for spray granulation is obtained;

[0010] 2) Preparation of hollow microspheres: The slurry is uniformly conveyed to a spray granulator for spray granulation, and the hollow microspheres are collected in a collector, and then burned to obtain rare earth oxide modified fly ash hollow microspheres.

[0011] According to some preferred embodiments of the present invention, the dispersant in step 1) is one of ammonium polyacrylate and ammonium polymethacrylate, and the pH of the system is maintained at 9 during the ball milling process so that COO in the dispersant - The groups dissociate completely.

[0012] According to some preferred embodiments of the present invention, the ball milling is stopped in the ball mill stirring tank after the powder particle size in the ball milling liquid is less than 1.5 μm.

[0013] According to some preferred embodiments of the present invention, in step 1), the contents of the components in the fly ash are as follows, measured in percentage: SiO2 is 33-60%, Al2O3 is 16-40%, Fe2O3 is 1.5-17%, CaO is 0.8-11%, MgO is 0.7-2%, Na2O is 0.2-1.5%, K2O is 0.7-2.9%, MnO is 0-0.1%, P2O5 is 0-0.5%, SO3 is 0-1.29%, TiO2 is 0-1.10%, and the loss on ignition is 1.2-10%; in the mixed powder, the mass percentage of fly ash is 90%-95%.

[0014] According to some preferred embodiments of the present invention, in step 1), the rare earth oxide is La2O3, CeO2 and La 0.36 Ce 0.64 O 1.82 One of the mixed powders, the mass percentage of rare earth oxide is 5%-10%.

[0015] According to some preferred embodiments of the present invention, the mass ratio of the mixed powder to the dispersant is 1:0.001; the mass ratio of deionized water to the dispersant is 0.5-1:0.001; and the mass ratio of the dispersant to the binder is 1:20.

[0016] According to some preferred embodiments of the present invention, the binder in step 1) is one of polyvinyl alcohol (PVA) and octylphenol polyoxyethylene ether (Triton X-100).

[0017] According to some preferred embodiments of the present invention, in step 2), the inlet temperature of the spray granulator is controlled to be 150-180° C. Further, the burning temperature is 900° C.-1100° C.

[0018] In a second aspect, the present invention provides rare earth oxide modified fly ash hollow microspheres prepared by the method, wherein the rare earth oxide modified fly ash hollow microspheres have a bulk density of 0.60-0.65 g / cm 3 , particle size D 50 The wall thickness is 25-35μm, the wall thickness is 1000-1500nm, the compressive strength is 6.5-8.5MPa, and the room temperature thermal conductivity is 0.075-0.095W / (m·K).

[0019] Compared with the prior art, the beneficial effects of the present invention include:

[0020] 1) In order to improve the dispersion of fly ash and rare earth oxide mixed powder in the ball milling liquid, the present invention adds COO - The anionic dispersant of the group, because when the pH of polyacrylate and ammonium methacrylate in the solution is greater than 8.5, COO - The groups are completely dissociated, so the pH value of the ball milling solution is adjusted to 9.

[0021] 2) Since the maximum saturation capacity of the powder adsorbing the dispersant decreases with the increase of pH, when the pH value of the ball milling solution is 9, the surface charge of the particles is negative, and COO - The groups are completely dissociated, so the adsorption of dispersants on the particle surface only occurs on a few positive sites, and the saturation capacity of the particles to adsorb dispersants is low. Adding excessive dispersants will increase the ionic strength in the ball milling liquid, destroying the stability of the ball milling liquid, so the present invention controls the amount of dispersants added. In the spray drying process of the slurry with good dispersibility, due to the capillary force, the particles and the binder migrate to the droplet surface and form a rigid shell on the droplet surface, resulting in the formation of hollow particles.

[0022] 3) During the high-temperature calcination process, the polarization characteristics of rare earth oxide reduce the activation energy of the solid-phase reaction of fly ash, thereby reducing the sintering temperature and the formation temperature of the mullite phase. It also has a good inhibitory effect on grain growth. Rare earth oxide promotes the filling of most of the glassy material into the crystal gap and obtains the lowest porosity and the most compact structure. The pores of the shell of the hollow microspheres with added rare earth oxide are smaller and evenly distributed, while the pores of the shell of the hollow microspheres without added rare earth oxide are larger. The shell of the hollow microspheres modified by rare earth oxide is denser, which significantly improves the compressive strength of the hollow microspheres.

[0023] 4) The present invention controls the calcination temperature to be 900°C-1100°C; at a temperature of 1000°C, La2O3 and CeO2 can easily react with active oxygen such as SiO2, Al2O3 and Fe2O3 in fly ash to form low-melting point compounds such as La2(SiO3)3, Ce2(SiO3)3, LaAlO3, CeAlO3, Al2Ce4O9, etc. These compounds tend to form a liquid phase on the surface of the particles, making them easy to rearrange, thereby improving the sintering strength; in addition, the alkali metal oxides contained in the fly ash melt at 1040°C, increasing the liquid phase, and a large amount of liquid phase improves the wettability of the particles, fills the pores between the particles, thereby passivating intergranular cracks and improving the bending strength; in addition, the amount of rare earth oxide added and the calcination temperature can be adjusted according to different application fields, and hollow microspheres with high porosity and dense shells can be prepared.

[0024] 5) The fly ash and rare earth oxide mixed powder in the slurry prepared by the present invention has a high concentration, which reduces the evaporation of water in the spray granulation process, improves the ability to produce hollow microspheres, and reduces energy consumption. At the same time, La2O3 and CeO2 can partially replace the ions of the fly ash compound at high temperature, and together with them, cause the lattice distortion of the fly ash compound, thereby improving the high-temperature activity of the fly ash. La2O3 and CeO2 react with SiO2 in the fly ash to generate lanthanum silicate and cerium silicate. Lanthanum silicate and cerium silicate decompose into liquid SiO2 and solid La2O3 and CeO2 at high temperature. La2O3 and CeO2 react with alumina to generate rare earth aluminate, and promote the formation of mullite whiskers at the same time. The thermal conductivity of rare earth modified fly ash is reduced by more than 10% compared with unmodified fly ash, and the thermal conductivity decreases with the increase of rare earth oxide addition. The rare earth oxide modified fly ash hollow microspheres prepared by the spray granulation method of the present invention can not only solve the shortage of natural hollow floating beads in the market, but also solve the stacking and pollution problems of coal-fired plant wastes, and recycle solid waste resources, which will surely create huge economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the SEM image of La2O3 modified fly ash hollow microspheres prepared in Example 1 of the present invention.

[0026] Figure 2 This is the SEM image of CeO2 modified fly ash hollow microspheres prepared in Example 2 of the present invention.

[0027] Figure 3 La prepared in Example 3 of the present invention 0.36 Ce 0.64 O 1.82 SEM image of modified fly ash hollow microspheres.

[0028] Figure 4This is a SEM image of the fly ash hollow microspheres prepared in Comparative Example 1 of the present invention.

[0029] Figure 5 The La prepared in Example 3 of the present invention 0.36 Ce 0.64 O 1.82 SEM image of the locally enlarged surface of modified fly ash hollow microspheres.

[0030] Figure 6 This is a partially enlarged SEM image of the surface of the fly ash hollow microspheres prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described and illustrated below in conjunction with specific embodiments. The embodiments are merely exemplary of the present disclosure and do not define the scope of limitation. The technical features of each embodiment of the present invention may be combined accordingly without conflicting with each other.

[0032] Example 1

[0033] (1) Preparation of fly ash and La2O3 mixed powder slurry: 100L of deionized water and 0.1kg of ammonium polyacrylate were added to a ball mill stirring tank. After stirring and dispersing evenly, the ball mill was turned on and 95kg of fly ash and 5kg of La2O3 powder were gradually added. The pH value of the ball milling liquid was controlled at 9 during the ball milling process. When the powder particle size in the ball milling liquid was less than 1.5μm, the ball milling was stopped and the ball milling liquid was transported to a spray granulation dispersion tank. 2kg of PVA was added and after high-speed dispersion, a spray granulation slurry containing 49.48% of fly ash and La2O3 mixed powder was obtained.

[0034] (2) Preparation of La2O3-modified fly ash hollow microspheres: The spray granulator was turned on, and the inlet temperature was controlled at 150°C. The slurry was uniformly conveyed into the spray granulator, and the hollow microspheres were collected in a collector. The hollow microspheres were then calcined at 1100°C to obtain La2O3-modified fly ash hollow microspheres. Figure 1 The SEM image of the obtained La2O3-modified fly ash hollow microspheres is shown in Figure 1. As can be seen from the figure, the obtained La2O3-modified fly ash hollow microspheres are composed of irregular particles and submicron fly ash balls bonded into a hollow microsphere shell, and the spherical particles are monodispersed without collapse or breakage.

[0035] The obtained La2O3 modified fly ash hollow microspheres were characterized, and the bulk density was tested by the measuring cylinder method, the particle size was tested by BT-9300ST laser particle size analyzer, the wall thickness was tested by focused ion beam scanning electron microscope, the compressive strength was tested by powder compressive strength test method (GB / T-43091-2023), and the room temperature thermal conductivity was tested by Hot Disk method / transient flat plate heat source method.

[0036] The bulk density of the La2O3-modified fly ash hollow microspheres prepared in Example 1 is 0.61 g / cm 3 , particle size D 50 The wall thickness is 31μm, the wall thickness is 1030nm, the compressive strength is 8.28MPa, and the room temperature thermal conductivity is 0.077W / (m·K).

[0037] Example 2

[0038] (1) Preparation of fly ash and CeO2 mixed powder slurry: 100 L of deionized water and 0.2 kg of ammonium polymethyl acrylate were added to a ball mill stirring tank. After stirring and dispersing evenly, the ball mill was turned on and 180 kg of fly ash and 20 kg of CeO2 powder were gradually added. The pH value of the ball milling liquid was controlled at 9 during the ball milling process. When the powder particle size in the ball milling liquid was less than 1.5 μm, the ball milling was stopped and the ball milling liquid was transported to a spray granulation dispersion tank. 4 kg of Triton X-100 was added. After high-speed dispersion, a fly ash and CeO2 mixed powder spray granulation slurry containing 65.75% was obtained.

[0039] (2) Preparation of CeO2-modified fly ash hollow microspheres: Turn on the spray granulator, control the inlet temperature at 180°C, transport the slurry to the spray granulator at a uniform speed, collect the hollow microspheres in a collector, and then calcine at 900°C to obtain CeO2-modified fly ash hollow microspheres. Figure 2 This is a SEM image of the CeO2-modified fly ash hollow microspheres of Example 2 of the present invention. As can be seen from the figure, the obtained CeO2-modified fly ash hollow microspheres are formed by bonding irregular particles and submicron fly ash balls into a hollow microsphere shell, and the spherical particles are monodispersed without collapse or breakage.

[0040] The obtained CeO2 modified fly ash hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0041] The bulk density of the CeO2-modified fly ash hollow microspheres prepared in Example 2 is 0.65 g / cm 3 , particle size D 50 The wall thickness is 29.3 μm, the wall thickness is 1470 nm, the compressive strength is 6.56 MPa, and the room temperature thermal conductivity is 0.092 W / (m·K).

[0042] Example 3

[0043] (1) Fly ash and La 0.36 Ce 0.64 O 1.82 Preparation of mixed powder slurry: Add 100L deionized water and 0.15kg ammonium polymethacrylate into the ball mill stirring tank, stir and disperse evenly, then start the ball mill and gradually add 138.75kg fly ash and 11.25kg La 0.36 Ce0.64 O 1.82 The pH value of the ball milling liquid was controlled at 9 during the ball milling process. When the particle size of the powder in the ball milling liquid was less than 1.5 μm, the ball milling was stopped. The ball milling liquid was transported to the spray granulation dispersion tank, 3 kg of PVA was added, and after high-speed dispersion, a granulated powder containing 59.25% fly ash and La was obtained. 0.36 Ce 0.64 O 1.82 Mixed powder spray granulation slurry.

[0044] (2)La 0.36 Ce 0.64 O 1.82 Preparation of modified fly ash hollow microspheres: Turn on the spray granulator, control the inlet temperature at 165℃, transport the slurry to the spray granulator at a uniform speed, collect the hollow microspheres in the collector, and then burn them at 1000℃ to obtain La 0.36 Ce 0.64 O 1.82 Modified fly ash hollow microspheres. Figure 3 Example 3La of the present invention 0.36 Ce 0.64 O 1.82 SEM image of modified fly ash hollow microspheres. 0.36 Ce 0.64 O 1.82 The modified fly ash hollow microspheres are composed of irregular particles and submicron fly ash balls bonded together to form a hollow microsphere shell. The spherical particles are monodispersed and no collapse or breakage is observed.

[0045] For the income 0.36 Ce 0.64 O 1.82 The modified fly ash hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0046] Example 3 Preparation of La 0.36 Ce 0.64 O 1.82 The bulk density of modified fly ash hollow microspheres is 0.63g / cm 3 , particle size D 50 The wall thickness is 28.4 μm, the wall thickness is 1300 nm, the compressive strength is 7.53 MPa, and the room temperature thermal conductivity is 0.082 W / (m·K).

[0047] Comparative Example 1

[0048] (1) Preparation of fly ash slurry: 100 kg of fly ash replaces 95 kg of fly ash and 5 kg of La2O3 powder, and the rest is the same as in Example 1 (1).

[0049] (2) Preparation of fly ash hollow microspheres: same as (2) in Example 1. Figure 4 The SEM image of the obtained fly ash hollow microspheres is shown in Figure 1. As can be seen from the image, the obtained fly ash hollow microspheres are composed of irregular particles and submicron fly ash balls bonded into a hollow microsphere shell, and the spherical particles are monodispersed without collapse or breakage.

[0050] The obtained fly ash hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0051] Example 1 compared with Comparative Example 1: Compared with Comparative Example 1, Example 1 has similar hollow microsphere particle size and wall thickness, but the bulk density is increased by 1.7%, the room temperature thermal conductivity is reduced by 27.01%, and the compressive strength is increased by 4%.

[0052] Comparative Example 2

[0053] (1) Preparation of fly ash slurry: 150 kg fly ash replaces 138.75 kg fly ash and 11.25 kg La 0.36 Ce 0.64 O 1.82 Powder, other parts are the same as those in Example 3 (1).

[0054] (2) Preparation of fly ash hollow microspheres: same as (2) in Example 3.

[0055] Figure 5 is La obtained in Example 3 0.36 Ce 0.64 O 1.82 SEM image of the partially enlarged surface of the modified fly ash hollow microspheres. Figure 6 This is a partially enlarged SEM image of the surface of the fly ash hollow microspheres obtained in Comparative Example 2. Figure 5 It can be seen that La 0.36 Ce 0.64 O 1.82 The particle surface of the modified fly ash hollow microsphere shell is wrapped by the formed liquid phase. Figure 6 The particle surface in the shell layer of fly ash hollow microspheres is not completely covered by the liquid phase; adding rare earth oxide to fly ash forms more liquid phase at high temperature than without adding rare earth oxide. A large amount of liquid phase improves the wettability of the particles, fills the pores between the particles and coats the particle surface, thereby improving the mechanical properties of the hollow microspheres.

[0056] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing hollow fly ash microspheres modified with rare earth oxide, characterized in that: The method comprises the following steps: 1) Slurry preparation: Add deionized water and COO into a ball mill stirring tank. - After the dispersion is evenly dispersed, the ball mill is turned on and fly ash and rare earth oxide mixed powder are gradually added. During the ball milling process, the pH value of the ball milling liquid is controlled to make the COO - The groups are completely dissociated. When the particle size of the powder in the ball milling liquid is smaller than the set value, the ball milling is stopped, and the ball milling liquid is transported to the spray granulation dispersion tank, and a binder is added. After high-speed dispersion, the slurry required for spray granulation is obtained; 2) Preparation of hollow microspheres: The slurry is uniformly conveyed to a spray granulator for spray granulation, and the hollow microspheres are collected in a collector, and then burned to obtain rare earth oxide modified fly ash hollow microspheres.

2. The method for preparing rare earth oxide modified fly ash hollow microspheres according to claim 1, characterized in that: In step 1), the dispersant is one of ammonium polyacrylate and ammonium polymethacrylate. During the ball milling process, the pH of the system is maintained at 9 to allow the COO in the dispersant to - The groups dissociate completely.

3. The method for preparing rare earth oxide modified fly ash hollow microspheres according to claim 1, characterized in that: In the ball mill stirring tank, ball milling is stopped after the powder particle size in the ball milling liquid is less than 1.5 μm.

4. The method for preparing rare earth oxide modified fly ash hollow microspheres according to claim 1, characterized in that: In step 1), the contents of the components in the fly ash are as follows, measured in percentage: SiO2 is 33-60%, Al2O3 is 16-40%, Fe2O3 is 1.5-17%, CaO is 0.8-11%, MgO is 0.7-2%, Na2O is 0.2-1.5%, K2O is 0.7-2.9%, MnO is 0-0.1%, P2O5 is 0-0.5%, SO3 is 0-1.29%, TiO2 is 0-1.10%, and the loss on ignition is 1.2-10%; in the mixed powder, the mass percentage of fly ash is 90%-95%.

5. The method for preparing rare earth oxide modified fly ash hollow microspheres according to claim 1, characterized in that: In step 1), the rare earth oxides are La2O3, CeO2 and La 0.36 Ce 0.64 O 1.82 One of the mixed powders, the mass percentage of rare earth oxide is 5%-10%.

6. The method for preparing rare earth oxide modified fly ash hollow microspheres according to claim 1, characterized in that: The mass ratio of the mixed powder to the dispersant is 1:0.001; the mass ratio of deionized water to the dispersant is 0.5-1:0.001; and the mass ratio of the dispersant to the binder is 1:

20.

7. The method for preparing rare earth oxide modified fly ash hollow microspheres according to claim 1, characterized in that: In step 1), the binder is one of polyvinyl alcohol (PVA) and octylphenol polyoxyethylene ether (Triton X-100).

8. The method for preparing rare earth oxide modified fly ash hollow microspheres according to claim 1, characterized in that: In step 2), the inlet temperature of the spray granulator is controlled at 150-180°C.

9. The method for preparing rare earth oxide modified fly ash hollow microspheres according to claim 1, characterized in that: In step 2), the calcination temperature is 900°C-1100°C.

10. A rare earth oxide modified fly ash hollow microsphere prepared by the method according to any one of claims 1 to 9, characterized in that: The loose packing density of the rare earth oxide modified fly ash hollow microspheres is 0.60-0.65 g / cm 3 , particle size D 50 The wall thickness is 25-35μm, the wall thickness is 1000-1500nm, the compressive strength is 6.5-8.5MPa, and the room temperature thermal conductivity is 0.075-0.095W / (m·K).

Citation Information

Patent Citations

  • Method and device for preparing hollow ceramic microspheres

    CN101870588B

  • Preparation method of fly ash artificial hollow floating beads

    CN104310787A

  • A method for reducing the firing temperature of high-refractory ceramsite by using rare earth oxides

    CN117229078B

  • Process and device for the preparation of hollow microspheres comprising centrifugal atomization

    US8845936B2

  • Method for preparing foamed ceramic insulation board by coal ash

    CN101597178A